Does ESG performance promote vitality of capital market? Analysis from the perspective of stock liquidity - Chen, Ran; Liu, Yirong; Jiang, Yalin; Liu, Jiamin (Frontiers in Environmental Science, 2023)
Environmental, Social, and Governance (ESG) is changing from a concept to corporate soft power. Can this improve corporate performance in capital markets? There is little literature linking ESG performance to stock liquidity. Therefore, It is of urgent theoretical and practical importance to study the impact of ESG performance on stock liquidity. Using Chinese A-share listed companies from 2015 to 2020 as a sample to empirically examine the impact of ESG performance on stock liquidity and its mechanism. We find that ESG performance has a significant positive impact on listed companies’ stock liquidity. This conclusion was validated after conducting a series of robustness tests. Mechanism analysis shows that ESG performance can promote stock liquidity by reducing agency costs, increasing the proportion of foreign ownership, and improving corporate reputation. The heterogeneity analysis shows that ESG performance in state-owned enterprises, heavily polluting enterprises, and enterprises in areas with low degrees of marketisation has a more significant positive promoting effect on stock liquidity. This study expands the research on ESG performance and has implications for promoting the development of ESG practices.